2015
DOI: 10.1007/s10479-015-2065-4
|View full text |Cite
|
Sign up to set email alerts
|

Delay analysis and optimality of the renewal access protocol

Abstract: For many years, the IEEE 802.11 distributed coordination function (DCF) has been widely used as a dominant medium access control (MAC) protocol in wireless networks and a large number of works have been done for analyzing and improving its performance. In our earlier work, as a substitute of the IEEE 802.11 DCF, a simple MAC protocol, called the renewal access protocol (RAP), is proposed. The RAP adopts all of the legacy 802.11 standard but the backoff stage feature. Each terminal selects its backoff counter v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The latency of an SU packet represents the time it takes from when the SU packet enters the system until it successfully leaves the system. By using Little's Law 31,32 , the average latency of SU packets (đť›˝) is provided as follows:…”
Section: Average Latency Of Su Packetsmentioning
confidence: 99%
“…The latency of an SU packet represents the time it takes from when the SU packet enters the system until it successfully leaves the system. By using Little's Law 31,32 , the average latency of SU packets (đť›˝) is provided as follows:…”
Section: Average Latency Of Su Packetsmentioning
confidence: 99%
“…To analyze queuing delay, we tag a station and consider the worst case for this tagged station where all other stations are saturated. In [44], leveraging effective bandwidth theory, it is shown that the queue overflow probability in steady state…”
Section: Appendix B Delay Analysismentioning
confidence: 99%